2017
DOI: 10.1186/s12936-017-1914-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacogenetics on plasma lumefantrine pharmacokinetics and malaria treatment outcome in pregnant women

Abstract: BackgroundPregnancy has considerable effects on the pharmacokinetic properties of drugs used to treat uncomplicated Plasmodium falciparum malaria. The role of pharmacogenetic variation on anti-malarial drug disposition and efficacy during pregnancy is not well investigated. The study aimed to examine the effect of pharmacogenetics on lumefantrine (LF) pharmacokinetics and treatment outcome in pregnant women.MethodsPregnant women with uncomplicated falciparum malaria were enrolled and treated with artemether-lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…The main findings include the following: 1) significantly lower day 7 LF plasma concentration in pregnant compared with nonpregnant women, 2) significant association of CYP3A5*1/*1 genotype and low body weight with low day 7 LF plasma concentration, and 3) low day 7 LF plasma concentration as a significant predictor of treatment failure. To date, there are limited studies investigating the effect of CYP3A and ABCB1 genotype on LF concentration and malaria treatment outcome Vos et al, 2017), and only one small sample size study reported effect of genotype on LF plasma concentration in pregnant women (Mutagonda et al, 2017). Therefore, the present study described the effect of pregnancy and CYP3A genotype on day 7 LF plasma concentration and malaria treatment outcome.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The main findings include the following: 1) significantly lower day 7 LF plasma concentration in pregnant compared with nonpregnant women, 2) significant association of CYP3A5*1/*1 genotype and low body weight with low day 7 LF plasma concentration, and 3) low day 7 LF plasma concentration as a significant predictor of treatment failure. To date, there are limited studies investigating the effect of CYP3A and ABCB1 genotype on LF concentration and malaria treatment outcome Vos et al, 2017), and only one small sample size study reported effect of genotype on LF plasma concentration in pregnant women (Mutagonda et al, 2017). Therefore, the present study described the effect of pregnancy and CYP3A genotype on day 7 LF plasma concentration and malaria treatment outcome.…”
Section: Discussionmentioning
confidence: 88%
“…In the pharmacogenetics analysis, genomic DNA was isolated in whole-blood samples using QIAamp DNA Midi Kit (Qiagen GmbH, Hilden, Germany), according to the manufacturer's instructions. Genotyping for the common functional variant alleles for ABCB1 c.3435C.T and ABCB1 c.4036A.G (rs3842), CYP3A4*1B, CYP3A5*3, CYP3A5*6, and CYP3A5*7, which have been reported to be relevant for LF disposition (German and Aweeka, 2008;Djimdé and Lefèvre, 2009), was carried out at the Division of Clinical Pharmacology, Department of Laboratory Medicine, Karolinska Institutet, Sweden, as previously described (Mutagonda et al, 2017). The Quant Studio 12 K Flex Real-Time PCR system (Life Technologies Holding, Singapore) was used for genotyping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few recent studies have investigated the pharmacogenetics of antimalarial drugs and its relevance for antiretroviral and antimalarial drug interaction in HIV–malaria coinfected patients receiving dual therapy in Africa . Lumefantrine, a long‐acting antimalarial drug, is metabolized by CYP3A4, an enzyme inducible by efavirenz .…”
Section: African Pharmacogenomics Research Consortium: Focus On Hiv mentioning
confidence: 99%